The emperor and the elephant: Christians and Muslims in the age of Charlemagne - Ottewill-Soulsby, Sam (Princeton University Press, 2023)
Chapter 1. Introduction -- Diplomacy -- Political Context -- Sources -- Chapter 2. Perception and Practice in Carolingian Diplomacy with the Islamic World -- Problems of Perspective -- Considering the Other -- Christ and Belial -- Envoys -- Travel -- Reception -- Gifts -- Eating the Fish -- Chapter 3. Carolingian Diplomacy with the 'Abbāsid Caliphate -- Existential Questions -- Motivations -- The Alliance System -- Patriarchs and Politics -- Prestige Diplomacy -- First Contact: Pippin III and al-Manṣūr (767-768) -- Charlemagne and Hārūn al-Rashīd -- The Elephant in the Room -- The End of Carolingian Diplomacy with the ʿAbbāsid Caliphs (831) -- Chapter 4. Carolingian-Umayyad Diplomacy, Part 1: 751-820 -- The Frontier -- The Beginning of Carolingian Relations with the Umayyads, 751-793 -- Sulaymān, Charlemagne, and the Roncesvalles Campaign, 777-781 -- An Unusual Proposition -- My Girona, 781-793 -- 751-793 Conclusion -- The Franks on the Offensive, 796-812 -- Useless Peace, 810-820 -- Conclusion -- Chapter 5. Carolingian-Umayyad Diplomacy, Part 2: 820-864 -- Disaster on the Frontier, 820-830 -- Leaders and Tribunes -- Lights in the Sky -- Charles the Bald and Umayyad Spain, 840-864 -- The Son of Evil, 847-851 -- Rebels and Vikings, 863-864 -- The Third King of Spain -- The Martyrs of Córdoba -- The End of Carolingian-Umayyad Diplomacy -- Chapter 6. The Central Mediterranean: The Limits of Carolingian Diplomacy with the Islamic World -- The Second Part of the World: Charlemagne and North Africa -- All-Out War: The Emirates of Italy -- Dogs in the Nighttime -- Conclusion. Death of an Elephant -- Bibliography -- Index.